Tax policy and the location decision of firms - Bernd Genser; Andreas Haufler (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1996)
An optimal taxation approach is employed to discuss the interaction between factor and commodity taxes for a small open economy when profit-earning firms are mobile internationally. In this framework, a destination-based commodity tax is shown to be superior to an origin-based VAT from an efficiency perspective. Furthermore, in the absence of co-ordination measures the small country finds it optimal to charge a zero effective tax rate on corporate profits. This provides an argument for an increased role of the EU in the field of capital taxation if mobility costs within Europe are systematically lower than costs for outside investments. – – Anhand eines Optimalsteueransatzes wird das Zusammenwirken von Faktor- und Gütersteuern in einer kleinen offenen Volkswirtschaft untersucht, wenn die international mobilen Firmen reine Profite erwirtschaften können. In diesem ökonomischen Modellrahmen erweist sich eine bestimmungslandbasierte Mehrwertsteuer einer ursprungslandbasierten aus Effizienzgründen überlegen. Ohne internationale Koordinierungsmaßnahmen ist es für das kleine Land optimal, die Körperschaftsprofite mit einer effektiven Steuerbelastung von null zu belegen. Der theoretische Befund signalisiert Handlungsbedarf für die EU auf dem Gebiet der Kapitalbesteuerung, wenn die Mobilitatskosten für Firmen innerhalb des Binnenmarkts systematisch niedriger sind als Mobilitatskosten für die Verlagerung von Firmen zwischen der EU und Drittländern.
Keywords: 330